RESPON TANAMAN PADI SAWAH (Oryza sativa L.) VARIETAS CIHERANG TERHADAP TAKARAN PUPUK KANDANG AYAM DAN URIEN KELINCI - Yudi Yusdian, Endang Kantikowati, dan Rijal Hadipraja (Program Studi Agroteknologi Faperta UNIBBA, 2021)
Tabel 1. Luas Panen, Produksi, dan Produktivitas Tanaman Padi di Indonesia dari Tahun 2013 s/d Tahun 2017 Data Statistik Tanaman Padi Tahun 2013 Tahun 2014 Tahun 2015 Tahun 2016 Tahun 2017 Luas Panen (Ha) 12.672 12.666 13.029 13.985 14.633 Produksi (Ton) 67.392 67.102 71.766 75.483 77.603 Produktivitas (Ton/Ha) 5,318 5,298 5,508 5,397 5,303 Sumber : Badan Pusat Statistika dan Kementrian Pertanian 2018 The study aims to determine the effect of chicken manure dosage and rabbit urine concentration on the growth and yield of rice plants (Oryza sativa L.) Ciherang varieties. The study was conducted in the month May to August 2019, in Kebontiwu Village, Padaulun Village, Majalaya District, Bandung Regency, West Java Province. This research used factorial randomized block design (RBD) with 3 replications. Factor I: Dosage of chicken manure (k1 = 2.5 tons / ha, k2 = 5 tons / ha, k3 = 7.5 tons / ha). Factor II: Rabbit urine concentration (u1 = 25 ml / L, u2 = 30 ml / L, u3 = 35 ml / L). The results showed that the treatment of chicken manure dosage and rabbit urine concentration had a significantly different effect on the number of productive tillers and interactions effect on harvested unhusked rice and milled unhusked rice. The highest yields were shown by a combination of k2u2 treatment (dose of chicken manure 5 tons / ha and urine concentration of rabbits 30 ml / L) produced harvested unhusked rice 14.10 kg/ plot and milled unhusked rice 12.34 kg/ plot.